Anti-inflammatory effect of thyme on rheumatoid arthritis in animal model: Thyme alleviates arthritis inflammation - Blbas, Sana Seamand Sabir; Hiwa Ramadhan Fatah; Safia Sabr Ibrahim Blbas (Cellular and Molecular Biology, 2025)
Thyme (Thymus vulgaris) is a Mediterranean herb known for its culinary, cosmetic, and medicinal applications as it has been discovered that the plant has many clinical properties such as anti-inflammatory, anti-microbial, and antioxidant properties. Sandwich Elisa technique was used to determine the concentration of cytokines. Phenolic contents and other active compounds of thyme were analyzed by Gas Chromatography-Mass Spectrometry (GC-Mass). In this study 15 male adult albino rats were divided into 3 groups (n=5), group one (G1) was the control group which fed on basal diet. Group two (G2) was the Rheumatoid arthritis (RA) group in which the rats were inoculated with 0.1 ml of CFA (Complete Freund’s Adjuvant) yet fed on basal diet. Group three (G3) was the treatment group in which rats were inoculated with CFA along with the administration of thyme extract orally for 22 days. The results show that treatment with thyme extract significantly reduced proinflammatory cytokines IL-1 (interleukin-1), IL-6 (interleukin-6) and TNF- α (tumor-necrosis factor-alpha). Anti-inflammatory IL-10 (interleukin-10) showed a significant increase in the thyme-treated group. CD4 T (cluster of differentiation-4) cell levels showed a significant difference, while sCD14 (soluble cluster of differentiation-14) levels were non-significant in the thyme group compared to the RA group. Inflammatory markers (C-reactive proteins) CRP and (anti-cyclic citrullinated peptide) Anti-CCP antibodies were both significantly elevated in RA and significantly reduced by thyme treatment. Although body weight changes were statistically non-significant, they were visibly prominent. Paw edema was significantly decreased in the thyme-treated group. (Matrix-metalloproteinase) MMP-1 levels and neutrophil counts were both elevated in RA and significantly reduced following thyme extract treatment.